ENHANCING ENGINEERING EDUCATION THROUGH INDUSTRY-ACADEMIA COLLABORATION IN THE ’ENGINEERS IN SOCIETY’ COURSE - Nurul Noraziemah Mohd Pauzi; Che Maznah Mat Isa (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Engineering students frequently lack exposure to the real-world legal, ethical, and regulatory challenges they will face in their professional careers. Furthermore, the limitations of conventional classroom settings can restrict access to industry experts, hindering the delivery of contemporary and relevant knowledge. This study addresses the gap in engineering education concerning real-world legal, ethical, and regulatory challenges by integrating industry expertise into the "Engineers in Society" course through a collaborative teaching model. This study employs a mixed-methods approach, utilizing a qualitative document review to analyze the Engineers in Society course content and structure and a quantitative approach involving structured surveys to gather student feedback on learning outcomes attainment. These entrance-exit surveys include Likert-scale questions assessing students’ understanding of professional and ethical responsibilities, practical application skills, and overall preparedness for engineering roles. The course content is divided into four main areas: the Malaysian Legal System, Roles and Responsibilities of Engineers, Local and Federal Authority Regulations, and the Occupational Safety and Health Act. These topics are delivered online by legal experts, industry professionals, and regulatory representatives. Results indicate significant improvements in students’ comprehension of legal and regulatory frameworks and a heightened awareness of ethical considerations. The integration of industry expertise provided valuable practical insights, enriching the educational experience and offering real-world perspectives. The online format facilitated interaction with a diverse range of experts, enhancing flexibility and accessibility. The study concludes that collaborative teaching models with industry integration effectively enhance engineering education, better preparing students for future professional challenges.